2009
DOI: 10.1038/modpathol.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1 expression correlates with favorable prognosis in ovarian cancers

Abstract: Aldehyde dehydrogenase 1 (ALDH1), a detoxifying enzyme responsible for the oxidation of intracellular aldehydes, was shown to play a role in the early differentiation of stem cells, through its role in oxidizing retinol to retinoic acid. It has been shown that ALDH1 is a predictor of poor clinical outcome in breast cancer. The authors hypothesized that the level of ALDH1 expression may be correlated with the clinical outcome of patients with ovarian cancer. Immunohistochemical staining of ALDH1 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
110
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 35 publications
16
110
4
3
Order By: Relevance
“…In the present study, we investigated potential alterations in the RA pathway and analyzed their clinical relevance. In contrast to findings in other tumor entities, [7][8][9][10][11][12][13][14] we observed a marked up-regulation of key molecules associated with increased RA availability and alternative, prosurvival RA usage in gliomas. This was accompanied by increased intratumoral levels of RA precursors and activated RA.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated potential alterations in the RA pathway and analyzed their clinical relevance. In contrast to findings in other tumor entities, [7][8][9][10][11][12][13][14] we observed a marked up-regulation of key molecules associated with increased RA availability and alternative, prosurvival RA usage in gliomas. This was accompanied by increased intratumoral levels of RA precursors and activated RA.…”
contrasting
confidence: 99%
“…[7][8][9][10][11][12][13][14] In particular, epithelial tumors, which originate from tissues that depend on a closely orchestrated balance between cellular proliferation and subsequent differentiation, show loss of RA signaling components involved in RA availability. This frequently includes altered expression of cellular retinolbinding protein 1 (CRBP1), an intracellular transport protein in charge of facilitating the uptake of RA precursor molecules, [7][8][9] and of aldehyde dehydrogenase 1A1 (ALDH1A1), which is capable of activating RA precursors into the active RA metabolite, 10,11 as well as of cellular retinoic acid binding protein 2 (CRABP2) and cellular retinoic acid binding protein 1 (CRABP1), two chaperone proteins that shuttle between different cellular compartments channeling RA to designated nuclear RA receptors or to endosomal degradation by cytochrome P450, family 26 members (CYP26), respectively. [12][13][14] In addition, recent studies on breast tumor cells revealed a pathological involvement of the intracellular transport protein fatty acid binding protein 5 (FABP5) in neoplastic RA signaling.…”
mentioning
confidence: 99%
“…Beyond alcohol metabolism, the role of ALDH1A1 is not yet understood. There are studies that report ALDH1A1 expression as a favorable prognostic factor in ovarian (11) and pancreatic cancer (12). However, contradicting data also show that positive cells have increased invasive and metastatic capabilities (13) and that ALDH1A1 expression is correlated with poor survival in breast cancer (14).…”
Section: Resultsmentioning
confidence: 99%
“…However, we detected that ALDH1A1 protein mainly in the cytoplasm of precancerous and cancer cells of esophagus, consistent with reports on breast and ovarian tumors. 7,20 Our data showed that in the low-grade esophageal squamous dysplasia, ALDH1A1-positive cells were distributed in the basal layer of the mucosa, suggesting normal mucosal stem cells as one of the sources for cancer stem-like cells. 21 Further, ALDH1A1 expression was positively correlated with the UICC stages, invasion depth and lymph node metastasis of esophageal squamous cell carcinoma and was associated with shorter survival of the patients.…”
Section: Discussionmentioning
confidence: 71%